Pengembangan Perangkat Lunak Layanan Online Kebun Raya Bogor Berbasis Web - Elke Cahya Putri; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Bogor Botanical Garden is one of the botanical gardens in Indonesia that is managed directly by the Plant Conservation Botanic Gardens-LIPI which has an area of 87 hectares. There are various types of plants and attractions in Bogor Botanical Garden. With the vastness of land owned, there are several problems that are felt by Bogor Botanical Garden's visitors, they are: the visitors do not know the location of the attraction to be visited, the visitors do not know the diversity of attractions, and the visitors do not know how to give a testimony to the manager. So far, the manager finds out the satisfaction level of the visitors simply by seeing visitor posts on the Bogor Botanical Gardens Facebook Fanpage page which is considered to be less valid in representing the satisfaction level of the visitors. So, a solution given to overcome these problems is by adding features to search the location of the attractions in the Bogor Botanical Garden, to display the list of tourist attractions, to save testimonials and to display a graph of visitors' satisfaction results from image detection using the Local Binary Pattern (LBP) algorithm. The result of the tests shows that unit testing, integration testing, and validation testing is 100% valid and the result of compatibility testing shows that the system can run on 8 types of web browsers.